Geomorphic origin and dynamics of deep, peat-filled, valley bottom wetlands dominated by palmiet (Prionium serratum) : a case study based on the Goukou Wetland, Western Cape - Job, Nancy Merle (Rhodes University, Faculty of Science, Department of Environmental Science, 2014)
The Goukou Wetland is a 700 ha unchannelled valley bottom wetland near the town of Riversdale in the Western Cape of South Africa. The wetland is approximately 16 km long and between 200 and 800 m wide, with peat deposits up to 8 m deep that get progressively shallower downstream. The Goukou Wetland is one of the last remaining intact peatlands of significant size in the Western Cape. However, there is increasing human pressure on these peat wetlands, where the dominant plant is palmiet (Prionium serratum), which is endemic to the Western and Eastern Cape Provinces of South Africa. Palmiet is viewed as a problem plant by farmers as it is believed to block waterways and promote inundation of arable land and infrastructure. Many landowners therefore actively remove palmiet from peatlands, threatening the integrity of these wetlands. Although the hydrogeomorphic origin of large, non-peat floodplain and valley bottom wetlands has been investigated in South Africa, unchannelled valley-bottom wetlands with deep peat accumulations are rare features and have not been well studied. The hydrogeomorphic factors leading to peat accumulation have been documented elsewhere in Southern Africa, where aggradation due to sedimentation along trunk streams may block a tributary stream, elevating the local base level of the tributary, creating the accommodation space for organic sedimentation. Alternatively, sedimentation along a trunk stream at the toe of a tributary stream may similarly block a trunk stream, promoting organic sedimentation along the trunk stream upstream of the tributary. This pattern of peat accumulation is associated with declining peat thickness upstream of the blocked valley. In the case of the Goukou Wetland, however, peat depth and organic content was found to increase consistently upstream from the toe to the head of the wetland. The Goukou Wetland was graded along its length, with gradient increasing consistently upstream in response to longitudinal variation in discharge. There was no clear relationship between peat formation and tributary streams blocking the wetland. Instead, the distribution of peat and the extent of the wetland appeared to be controlled by the plant palmiet, whose clonal nature and robust root, rhizome and stem system allowed it to grow from channel banks and islands into fast-flowing river channels, slowing river flows and ultimately blocking the channel. The promotion of diffuse flows within the dense, monospecific stands of palmiet creates conditions conducive to water retention and peat accumulation. By growing across the full width of the valley floor, the plant is able to constrict the stream, trapping sediment and slowing flows such that the fluvial environment is changed from a fast flowing stream to one with slow, diffuse flow. These processes appear to lead to the formation of organic sediment, accumulating to form a deep peat basin. The sustained input of water from the folded and fractured quartzite lithologies of the Cape Supergroup that make up the Langeberg Mountains, which provide the bulk of the water supply to the wetland, is also important in promoting permanent flooding in the wetland. A feature that characterized the wetland was the fact that bedrock across the valley beneath the peat deposits exhibited a remarkably uniform elevation. This suggests that over long periods of time (tens to hundreds of thousands of years), bedrock has been laterally planed across the valley floor. It is proposed that valley widening associated with lateral planning of Uitenhage Formation rocks has taken place during periods of episodic very high flows. During these episodes, erosion cuts into the peat wetland and valley sides, cutting to bedrock and planing the valley floor to a uniform elevation for a given distance from the head of the wetland. Periods of episodic degradation are followed by periods of renewed peat accumulation associated with palmiet establishment, such that the wetland valley is shaped by repeated cycles of cutting and filling. Palmiet can be considered an "ecosystem engineer" that is integral to the formation of these deep peat basins. Removal of palmiet from these systems is likely to have negative consequences for the wetland and its functions in that water storage will be reduced, erosion will increase dramatically, and the water-purification function of the wetlands will be lost. Management of these wetlands, which are close to the geomorphic threshold slopes for their size, is therefore essential if they are to be preserved for the benefit of human well-being.
Keywords: Wetlands -- South Africa -- Western Cape; Peatlands -- South Africa -- Western Cape; Peatland conservation -- South Africa -- Western Cape; Peatland management -- South Africa; Aquatic plants -- South Africa -- Western Cape; Geomorphology -- South Africa -- Western Cape